Clinical Development of PARP Inhibitors in Treating Metastatic Castration-Resistant Prostate Cancer - Adashek, Jacob J. (Cells, 2019)
The approval of upfront abiraterone for castration-sensitive prostate cancer and the approval of enzalutamide and apalutamide for non-metastatic castration-resistant prostate cancer have led to early utilization of potent androgen receptor (AR) signaling inhibitors in treating advanced prostate cancer. There is an unmet need to develop novel therapies beyond targeting AR signaling for metastatic castration-resistant prostate cancer (mCRPC). Poly (ADP-ribose) polymerase inhibitors (PARPi) belong to a class of targeted agents being developed for the treatment of homologous recombination repair (HRR) deficient tumors. Olaparib, rucaparib, niraparib, veliparib, and talazoparib were evaluated in early phase trials as a monotherapy for HRR-deficient mCRPC. Among them, olaparib and rucaparib have breakthrough designations for BRCA1/2-mutated mCRPC. Phase II studies also reported clinical activity of the PARPi and abiraterone combination and the PARPi checkpoint inhibitor combination in HRR-intact mCRPC. Ongoing phase III trials are testing these combinations as frontline or later line treatments for mCRPC. This review summarizes the critical clinical data as well as ongoing clinical trials for developing PARPi in treating mCRPC.